2006
DOI: 10.1186/1465-9921-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin induced peritonitis elicits monocyte immigration into the lung: implications on alveolar space inflammatory responsiveness

Abstract: These data, taken together, show that intraperitoneal endotoxin triggers a CCR2-dependent de novo recruitment of monocytes into the lungs of mice but this does not result in an accentuation of neutrophilic lung inflammation. This finding represents a previously unrecognized novel inflammatory component of lung inflammation that results from endotoxin-induced peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
(53 reference statements)
0
18
1
Order By: Relevance
“…The data of Steinmüller and colleagues showed that, in mice, the intraperitoneal endotoxin triggers the recruitment not only of granulocytes, but also of monocytes into the lungs, which amplifies the lung inflammatory responses with a "second-hit" endotoxin challenge intratracheally [44]. In our study, we injected LPS endotoxin intraperitoneally, but, in contrast of previous models, signs of septic shock syndrome could not be observed either clinically or histopathologically.…”
Section: Baltcontrasting
confidence: 83%
“…The data of Steinmüller and colleagues showed that, in mice, the intraperitoneal endotoxin triggers the recruitment not only of granulocytes, but also of monocytes into the lungs, which amplifies the lung inflammatory responses with a "second-hit" endotoxin challenge intratracheally [44]. In our study, we injected LPS endotoxin intraperitoneally, but, in contrast of previous models, signs of septic shock syndrome could not be observed either clinically or histopathologically.…”
Section: Baltcontrasting
confidence: 83%
“…Although i.p. injections of LPS also evoke acute lung injury, the pulmonary responses of animal (e.g., BAL fluid cytokine/chemokine profiles and BAL fluid cellular constituents) are different due to different LPS approaches (22,23). We cannot find reports on the use of a selective Src TK inhibitor, PP1, in i.t.…”
Section: N Uclear Factor B (Nf-b) Is Transcriptional Regulatorymentioning
confidence: 89%
“…It is generally held that monocytes/ macrophages play a central role in the host response against bacterial infections, although the published data on the role of monocytes/macrophages for pulmonary neutrophilia are complex and contradictory. For example, on the one hand, one study (35) reported that alveolar macrophages are a positive regulator endotoxin-induced neutrophil accumulation in the lung. On the other hand, another study (2) has shown that depletion of alveolar macrophages has no effect or even increases pulmonary recruitment of neutrophils in response to endotoxin (2).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are particularly sensitive to C-X-C motif (CXC) chemokines, including chemokine CXC ligand (CXCL)1, CXCL2, and CXCL5 (20). Although it is widely held that monocytes play an important role in systemic inflammation, the literature on the role of monocytes in controlling pulmonary neutrophilia is complex and partly contradictory (1,35). Thus, we decided to examine the role of blood monocytes for pulmonary accumulation of neutrophils as well as cytokine and chemokine formation in abdominal sepsis.…”
mentioning
confidence: 99%